2014
DOI: 10.1177/0145721714527518
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diabetes Health Literacy by Animation

Abstract: Purpose and Scope To produce a Spanish/English animated video about diabetes; to qualitatively assess cultural and linguistic appropriateness; and to test effectiveness at improving diabetes health literacy among Latino/Hispanics. Methods Participatory research and animation production methods guided development of the video. Cultural appropriateness was assessed through focused discussion group methods. A prospective randomized controlled trial tested the effectiveness of the Spanish version at improving di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 33 publications
1
94
0
1
Order By: Relevance
“…As health care providers, we can directly address many of the factors crucial for closing the CKD/ESRD disparities gap, and while other factors may seem beyond our reach, we should not turn a blind eye to those elements of institutionalized racism entrenched within the fabric of our society, such as social injustice and human indifference 11,61 . Examples of evidence-based initiatives to mitigate untoward effects of socioeconomic deprivation include expanding awareness of CKD in vulnerable communities and high-risk individuals such as through the National Kidney Foundation Early Evaluation Program or mobile clinics 6366 and implementing strategies to increase health literacy even among low-educational groups with or at risk for CKD with use of videos and/or novellas, 67,68 the use of social support such as social networks, 19 and primary intervention strategies including the use of lay health workers and patient navigators to address CKD and CKD risk factors ranging from diabetes to childhood chronic diseases 63,66,69,70 . Finally, we should not miss the opportunity to learn important lessons as we strive to advance the necessary policies to improve social welfare and health outcomes, as the existence of health inequities provides unique, unrecognized opportunities for understanding biologic, environmental, sociocultural, and health care system factors that can lead to improved clinical outcomes 4,5,9,60,61 .…”
Section: Resultsmentioning
confidence: 99%
“…As health care providers, we can directly address many of the factors crucial for closing the CKD/ESRD disparities gap, and while other factors may seem beyond our reach, we should not turn a blind eye to those elements of institutionalized racism entrenched within the fabric of our society, such as social injustice and human indifference 11,61 . Examples of evidence-based initiatives to mitigate untoward effects of socioeconomic deprivation include expanding awareness of CKD in vulnerable communities and high-risk individuals such as through the National Kidney Foundation Early Evaluation Program or mobile clinics 6366 and implementing strategies to increase health literacy even among low-educational groups with or at risk for CKD with use of videos and/or novellas, 67,68 the use of social support such as social networks, 19 and primary intervention strategies including the use of lay health workers and patient navigators to address CKD and CKD risk factors ranging from diabetes to childhood chronic diseases 63,66,69,70 . Finally, we should not miss the opportunity to learn important lessons as we strive to advance the necessary policies to improve social welfare and health outcomes, as the existence of health inequities provides unique, unrecognized opportunities for understanding biologic, environmental, sociocultural, and health care system factors that can lead to improved clinical outcomes 4,5,9,60,61 .…”
Section: Resultsmentioning
confidence: 99%
“…The findings echoed those of the narrative synthesis (see Table 2 ). All ethnically targeted studies took place in urban American settings, with nearly half (5/11) reportedly recruiting from economically deprived or medically underserved areas [ 56 , 57 , 60 , 61 , 65 ]. More than half (6/11) used phone calls as part of the intervention, although other telehealth media were also used.…”
Section: Resultsmentioning
confidence: 99%
“…Although only one study offered patients intervention-related equipment (laptop and telehealth peripherals) [ 57 ], six offered financial remuneration ranging from US $40 to US $60 cash or vouchers [ 55 , 59 , 61 - 63 , 65 ], with one trial additionally offering some patients up to US $200 for reducing their HbA 1c levels by a prespecified amount [ 62 ]. The ethnically targeted studies frequently reported tailoring interventions to their target demographic, including offering written and spoken aspects of the intervention in a language other than English [ 56 , 61 , 64 , 65 ], designing interventions through consultation and feedback from minority groups [ 55 - 58 , 60 , 65 ], and using interventionists drawn from the target cultural communities [ 55 , 61 , 64 , 65 ]. This latter point included building input from minorities into the recruitment strategy and/or piloting materials and procedures with them.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of reporting bias was not generally found, but this may reflect post-hoc addition or omission of intended study outcomes. Also, some studies only achieved statistical significance for outcomes by looking for improvements within subgroups, particularly individuals with the lowest levels of initial health literacy [ 28 , 29 , 43 ]. Subgroup analysis is helpful scientifically and justified given the potentially diverse educational needs of different population groups, but such findings need to be cautiously interpreted.…”
Section: Discussionmentioning
confidence: 99%